(untitled) (Communication & Society, 1998)
This article deals with the technological, strategic and communicative innovations which affect the possibilities of persuasion in advertising upon the pre sent-day structure of the media. The author restates a dichotomy which is a cross-section of the doctrine on adverti sing: Is advertising an essentially educa tional process, or are we rather contem plating a process of an informational character closely associated with the diffusion of news? The article defends an intermediate stance between those who defend the role of advertising as being informative, and those who defend it as being educational. Certainly, nowadays it seems necessary to repeat more than ever, but at the same time it is not good to repeat any thing. To believe that there exists a level of optimum frequency without taking into account the creative level of messages, the format or the means and vehicles used, would seem not to be adequate.